Um jogo de cartas : uma proposta de aprendizagem significativa para o ensino médio de conceitos relacionados à eletrização e a Lei de Coulomb - Silva, Beine José da (2015)
The learning process is always changing, and time is notorious realize the importance of recreational use as an alternative to support meaningful learning, and that permeates such transformations, but especially in view of the dynamic and fluid society in which students are included, mainly because it is a cyber-context, and thus, helping to develop both the intellectual side, cognitive, affective and social. The educational product developed also aims the creation and consolidation of a knowledge base, the main references the Theory of Meaningful Learning Review (TASC) to facilitate the learning process of Electrostatic concepts proposed in the game. The pupils, it is hoped, also the learning concepts by forming graphs, interest in relation to solving proposed puzzles in the game and to make individual or group decisions involving situations as the current challenges in the game, and although the educational product by forming concepts on the board is attitude change agent with respect to these claims, or to facilitate the learning of concepts and awaken the interest for the study of physics. The change attitude to these demands, minimization of environmental impacts and sustainable development, encouraging the emergence of future competent professionals for the sectors of human activities related to the above topics. The qualitative results of Contents learning showed that the educational product has the potential to contribute to learning, which aims on the covered topics. It is believed that the improvement of the natural sciences teaching quality and, in particular, under treated in this project, can greatly contribute to the future generation of students with a different perception of concepts learning mode, and realize that as learning by itself can seek personal learning more independently, and even propose strategies to new situations electrization and decisions taken individually or collectively with interventions and discussions among the game components. Students feel freer to discuss and answer your questions with colleagues and some teachers who participated in the process, and so ended up allowing a more positive attitude towards the rights and wrongs, so goes against one of the principles of significant critical learning. Another positive aspect of the game is the discipline, since the rules place limits in the classroom, but at the same time stimulates the decision-making and promotes self-esteem, maintain concentration and attention.